Effect of integrated use of organic manures with chemical fertilizers in the rice-rice cropping system and its impact on soil health (Bangladesh Journal of Agricultural Research, 2010)
A field experiment was conducted during 2003-2004 at Bangladesh Agricultural University farm, Mymensingh to evaluate the suitability of different sources of organic materials for integrated use with chemical fertilizers for the Boro-Fallow-T. Aman rice cropping pattern. The experiment was set up in a randomized complete block design (RCBD) with three replications. Eight-treatments, formulated from organic manure and chemical fertilizers have been imposed. The treatment combinations are T1: control, T2: 70% NPKS, T3: 100% NPKS, T4: 70% NPKS + rice straw (RS) @ 5 t/ha, T5: 70% NPKS + dhaincha (DH) @ 15 t/ha, Tb: 70% NPKS + mungbean residue (MBR) @ 10 t/ha, T7: 70% NPKS + cowdung (CD) @ 5 t/ha and T8: 70% NPKS + poultry manure (PM) @ 3 t/ha. Organic manure or crop residue was applied to T. Aman rice and their residual effects were observed in the following Boro rice. Application of 70% NPKS + PM produced the highest grain yield of T. Aman rice, which was identical to that obtained with 100% NPKS with no manure. In Boro season. application of 100% NPKS produced the highest grain yield of 6.87 t/ha, which was identical with the application of 70% NPKS + PM (6.57 t/ha). The total grain yield in the cropping pattern ranged from 5.14 t/ha in T1 (control) treatment to 12.29 t/ha in the 100% NPKS. The application of 3 t/ha PM with 70% NPKS (T8) produced the total yield of 12.09 t/ha followed by 11.59 t/ha in the treatment containing 10 t/ha MBR plus 70% NPKS (T6). It appears that the application of 3 t/ha PM once in a year with 70% NPKS can reduce the use of 30% NPKS as fertilizers. There were negative balances for N and K with the highest mining of K, while the balances for P and S were positive. The economic analysis reveals that most of the treatments produced BCR (benefit-cost ratio) of more than 3.0 showing that they all are economically viable. The integrated use of fertilizers and manure resulted in considerable improvement in soil health by increasing organic matter, available P, and S contents of soils. The overall findings of the study indicate that the integrated use of chemical fertilizer and manure is important for sustainable crop yield in a rice-rice cropping pattern. Key Words: Organic manures; chemical fertilizer; soil health. DOI: 10.3329/bjar.v34i1.5757Bangladesh J. Agril. Res. 34(1) : 81-90, March 2009